Kecemasan, Stres, dan Depresi pada Kekambuhan Gejala Gastritis diantara Narapidana Penyalahguna Narkoba di Bandung - Angga Wilandika; Wulan Nurazizah; Santy Sanusi (RSUP Dr. Kariadi, 2025)
BACKGROUND: Drug abuse inmates in correctional institutions undergo rehabilitation programs and are supervised according to the determined sentence, thus losing their freedom. This condition causes psychosocial problems such as anxiety, stress, and depression, which may be associated with physical issues, including the recurrence of gastritis symptoms. AIMS: To identify the correlation between anxiety, stress, and depression with recurrence of gastritis symptoms in drug abuse inmates at the correctional institution. METHOD: The study used a cross-sectional design and involved 34 inmates with a history of gastritis due to drug abuse. Purposive sampling was used to select the participants. The levels of anxiety, stress, and depression were measured using the Indonesian version of the Depression Anxiety Stress Scales (DASS-21). The Gastritis Recurrence Questionnaire evaluated the recurrence of gastritis symptoms in the inmates. The data was analyzed using descriptive statistics such as frequency distribution, and inferential analysis was conducted using the Kendal-tau test to identify correlations between the variables. RESULT: The study findings indicate a correlation between anxiety, stress, and depression and the recurrence of gastritis symptoms in inmates in correctional institutions (p-value < 0.05). Most inmates with a history of drug abuse experience psychosocial problems such as very high anxiety (29.4%) and severe stress (32.4%). At the same time, 73.5% do not experience depression. CONCLUSION: Psychosocial issues like anxiety, stress, and depression have been found to contribute to the likelihood of recurrence of gastritis symptoms in inmates. The higher the levels of anxiety, stress, and depression, the greater the possibility of recurrence of gastritis symptoms. Correctional institution managers should be prepared to address these psychosocial issues to help inmates reduce the recurrence of gastritis symptoms.